1979
DOI: 10.7326/0003-4819-90-4-533
|View full text |Cite
|
Sign up to set email alerts
|

The Compromised Host and Legionnaires' Disease

Abstract: Pneumonia caused by Legionnaires' disease bacterium was recognized in eight patients during a 7-month period. The patients were immunosuppressed by their underlying illness, corticosteroid therapy, and other exogenous immunosuppressive agents. Five of the patients had received immunosuppressive therapy for less than 16 days. Clinical presentation was similar to that of other bacterial pneumonias in compromised patients. Legionnaires' disease progressed to necrotizing pneumonia with abscess formation and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(23 citation statements)
references
References 6 publications
0
20
0
3
Order By: Relevance
“…We have found that egg yolk-grown L. pneumophila are resistant to killing by complement even in the presence of anti-L. pneumophila antibody and are inefficiently killed by human polymorphonuclear leukocytes in the presence of anti-L. pneumophila antibody and serum. These results, viewed in conjunction with the increased incidence of L. pneumophila infections in immunosuppressed patients (14)(15)(16), suggest that cell-mediated immunity may play an important role in host defense against L. pneumophila as it does against other intracellular parasites.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…We have found that egg yolk-grown L. pneumophila are resistant to killing by complement even in the presence of anti-L. pneumophila antibody and are inefficiently killed by human polymorphonuclear leukocytes in the presence of anti-L. pneumophila antibody and serum. These results, viewed in conjunction with the increased incidence of L. pneumophila infections in immunosuppressed patients (14)(15)(16), suggest that cell-mediated immunity may play an important role in host defense against L. pneumophila as it does against other intracellular parasites.…”
Section: Resultsmentioning
confidence: 65%
“…It affects all age groups, but particularly people over 30 yr, and men more often than women (8,13). It has a predilection for people who smoke or abuse alcohol, travellers, construction workers, and immunocompromised patients (6,10,(14)(15)(16), and it is probably spread by the airborne route (10). The case-fatality rate has been in the 15-20% range (10,17).…”
Section: Introductionmentioning
confidence: 99%
“…Legionnaires' disease has a predilection for immunocompromised patients (36)(37)(38)(39). Our findings suggest that a defect in cell-mediated immunity may be responsible for this by rendering such patients less capable of limiting the multiplication of Legionnaires' disease bacteria to which they are exposed.…”
Section: Cell-mediated Immunity May Be Viewed As Having An Afferent Amentioning
confidence: 78%
“…Legionnaires' disease in the immunocompromised host is often acquired from a nosocomial source. Fever, malaise, and a productive cough are common 8 . Radiographically, the presence of bilateral infiltrates and cavitation is relatively frequent.…”
Section: Pulmonary Infections In Cancer Patientsmentioning
confidence: 99%